Advancing forest functional process understanding through hyper-spatiotemporal LiDAR observation streams - Y. Wang; M. Campos; H. Sorokina; R. Echriti; T. Korpelainen; J. Hyyppä; E. Puttonen (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Understanding forest functional processes like carbon sequestration, water regulation, and habitat provision is crucial for evaluating ecosystem services and sustainable management. While satellite-based earth observation offers global coverage, its limited spatial-temporal resolution and weather dependency hinder detailed analysis. The LiDAR Phenology Station (LiPhe), established in 2020 by the Finnish Geospatial Research Institute of the National Land Survey of Finland is the world’s first permanent LiDAR system for forest observation, capturing dense 3D point clouds hourly even under adverse lighting conditions. Despite the challenges posed by processing its extensive dataset, with over three and a half years of continuous data, LiPhe offer transformative insights into the dynamics of boreal forest ecosystems by revealing the interconnection among local biotic and abiotic conditions, tree species, species- and tree- specific phenology, and species- and tree-specific growth strategy.